The structure and evaluation of educational research skills and accomplishments among rural teachers: Data from China - Feng, Luo; Yuxiang, Yao; Lihua, Qiu (Frontiers in Psychology, 2023)
The practice of educational research by rural teachers is highly valued and very important for their professional development and for the revitalization of rural education. This study explored the components of educational research activities among rural teachers (Study 1). Based on the results, a regional norm for Hunan province was formulated, and discriminant criteria were developed for the evaluation of educational research skills and accomplishments among rural teachers (Study 2). In Study 1, data from 892 Chinese rural teachers working at compulsory education schools in Hunan Province (a representative province in central China), divided into two samples, were found to support the constructs included in the measurement instrument. Exploratory and confirmatory factor analyses of the 33 items of the Rural Teachers’ Educational Research Self-rating Scale identified a first-order model with three factors: educational research on basic educational activities (BEA), educational research involving the creation of an educational community (CEC), and educational research involving the refinement and popularization of educational theory (RPE). Based on the results of Study 1, in Study 2, a set of norms for educational research skills and accomplishments among rural teachers was formulated based on the data from Hunan Province. This norm can serve as a reference standard for the evaluation of rural teachers’ educational research skills and accomplishments. The components of rural teachers’ educational research activities are discussed, and suggestions for the formulation of education policies are provided.